INTEGRATING ARTIFICIAL INTELLIGENCE INTO MEDICAL PHYSICS LABORATORY PRACTICE: NEW HORIZONS FOR LEARNING - Mamatqulov Bahodir Xatamovich (Uzbekistan Open Conference, 2026)
The article examines the prospects and methods of implementing artificial intelligence (AI) technologies in the educational process of laboratory classes in medical physics. Key areas of AI application are analyzed: automation of experimental data processing, modeling of complex biophysical processes, creation of adaptive feedback systems for students, and simulation of working with expensive medical equipment. Special attention is paid to how AI transforms the role of the teacher from a controller of results to a mentor, as well as ethical aspects and challenges related to dependence on algorithms. It is concluded that competent integration of AI improves the quality of training for future medical physicists and engineers, making learning more personalized and effective.
Keywords: artificial intelligence; medical physics; laboratory classes; machine learning; virtual simulators; data processing; educational technologies; personalized learning